Pantun as a Medium for Environmental Education and Ecological-Political Activism by Customary Institutions in Haruku Island - Harum, Diah Meutia; Sabara, Sabara; Kastanya, Helmina; Ma'rifat, Devi Fauziyah; Pattiserlihun, Selvone Christin; Alfian, Andi; Paais, Vikry Reinaldo (Forest and Society, 2025)
This research aims to examine the ecological values and political practice contained in pantun, particularly that used by the kewang, a customary or adat institution in Haruku Village, Central Maluku. In Haruku, pantun is used as a medium of enviromental education and ecological activism for the community, specifically the young generation. This study is expected to contribute to the reconstruction of a more eco-friendly civilization of the Archipelago by streamlining the potential of local traditions in promoting sustainability andconservation Haruku Village, in this study, becomes a role model and best practice of utilizing kewang as a customary institution, with the head of kewang as the central figure, in building ecological awareness and cultural-political strategy based on oral tradition and literature. By using the case study method and thematic analysis, this research discovered that the role of pantun in environmental activism carried out by kewang as a customary institution is very significant in the efforts of environmental conservation in Haruku. Eliza Marthen Kissya, as the head of kewang, made a strategy by producing pantun, which was then used as a medium for environmental education and cultural-political agenda to protect Haluku’s environment from external threat, as well as a medium for inheriting the ecological harmony, sustainability, and cultural resilience to the young generation of Haruku, especially the young generation who are prepared to become kewang in the future (kewang muda). The usage of pantun shows that traditional orality can be effectively utilized to support not only ecological harmony, but also cultivate an ideological, political, and cultural strategy. Therefore, local culture and natural conservation can be synergized in order to develop ecological awareness in the community as well as maintain the eco-political activism inherited in local culture and practices.